Maternal Fatty Acid Metabolism in Pregnancy and Its Consequences in the Feto-Placental Development - Duttaroy, Asim K.; Basak, Sanjay (Frontiers in Physiology, 2022)
During pregnancy, maternal plasma fatty acids are critically required for cell growth and development, cell signalling, and the development of critical structural and functional aspects of the feto-placental unit. In addition, the fatty acids modulate the early stages of placental development by regulating angiogenesis in the first-trimester human placenta. Preferential transport of maternal plasma long-chain polyunsaturated fatty acids during the third trimester is critical for optimal fetal brain development. Maternal status such as obesity, diabetes, and dietary intakes may affect the functional changes in lipid metabolic processes in maternal-fetal lipid transport and metabolism. Fatty acids traverse the placental membranes via several plasma membrane fatty acid transport/binding proteins (FAT, FATP, p-FABPpm, & FFARs) and cytoplasmic fatty acid-binding proteins (FABPs). This review discusses the maternal metabolism of fatty acids and their effects on early placentation, placental fatty acid transport & metabolism, and their roles in feto-placental growth and development. The review also highlights how maternal fat metabolism modulates lipid processing, including transportation, esterification, and oxidation of fatty acids.